2016
DOI: 10.1302/0301-620x.98b10.37957
|View full text |Cite
|
Sign up to set email alerts
|

International consensus on the definition and classification of fibrosis of the knee joint

Abstract: The development of standardised, accepted criteria for the diagnosis, classification and grading of the severity of post-operative fibrosis of the knee will facilitate the identification of patients for inclusion in clinical trials, the development of clinical guidelines, and eventually help to inform the management of this difficult condition. Cite this article: Bone Joint J 2016;98-B:1479-88.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 56 publications
1
107
0
2
Order By: Relevance
“…Postsurgical stiffness resulting from arthrofibrosis is not well defined and may involve reoperation using only soft tissue procedures without component removal or exchange. Such operations are not included in most joint registries, and a recent consensus statement suggested that joint registries were not suitable to identify joint fibrosis for this reason [34]. These examples of possible misclassifications could not be accounted for in the analyses of our study.…”
Section: Limitationsmentioning
confidence: 87%
“…Postsurgical stiffness resulting from arthrofibrosis is not well defined and may involve reoperation using only soft tissue procedures without component removal or exchange. Such operations are not included in most joint registries, and a recent consensus statement suggested that joint registries were not suitable to identify joint fibrosis for this reason [34]. These examples of possible misclassifications could not be accounted for in the analyses of our study.…”
Section: Limitationsmentioning
confidence: 87%
“…Most limiting in the shoulder, knee, hip, wrist, and ankle, the incidences of arthrofibrosis are remarkably high. In the United States alone, close to 3 million individuals are subjected to procedures attempting to alleviate arthrofibrosis every year ( Table 1) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). For instance, the incidence of knee arthrofibrosis cases that require surgical intervention is 14.5% after intraarticular (IA) fractures or other trauma (21).…”
mentioning
confidence: 99%
“…[26]. Consensus agreement was defined, in accordance with other published work, as a predetermined mean score of seven or greater (with fewer than 20% outliers, defined as a score of four or less) [28,29].…”
Section: Methodsmentioning
confidence: 96%
“…A combination of validated nominal group techniques and the Delphi process was applied, in accordance with the development of consensus statements published by other groups [25][26][27][28][29]. An overview of the process is summarised in Figure 1.…”
Section: Methodsmentioning
confidence: 99%